Paleomagnetic reconstruction of Coahuila, Mexico: the Late Triassic Acatita intrusives - Roberto S. Molina Garza (Geofísica Internacional, 2005)
The Acatita plutons intrude the upper Paleozoic of Las Delicias, southern Coahuila. We collected 96 samples from 15 sitesin two plutons from Valle El Sobaco and Sierra Los Remedios for paleomagnetic and 40Ar-39Ar analyses. Separates of hornblende(215.9 ±1.9 Ma, 2σ confidence level), biotite (217.3 ±1.2 Ma), and K-feldspar (205.6 ±1.4 Ma) yield nearly flat age spectraalthough none of the data satisfy strict plateau criteria, possibly reflecting slight alteration. The preferred ages are interpreted asfairly precise records of Late Triassic cooling of the plutonic suite, which has yielded concordant U-Pb Zircon ages ca. 220 Ma.Most samples yield north-directed and steep positive magnetizations similar to the late Cenozoic expected field direction. Somesamples, mostly from mafic enclaves, show northwest magnetization of shallow inclination (southeast at one site) with alternatingfields above ~30 mT and thermal demagnetization above ~400°C. The overall mean direction, corrected for 15° northeast dip ofthe overlying lower Cretaceous strata (dec=342.7°, inc=+4.2°; k=35.4, α95=9.4°, n=8 sites) indicates moderate counterclockwise(14°±8°) rotation with respect to the Late Triassic cratonic reference (reference pole: 57.5°N / 84°E), and moderate southwarddisplacement (7°±5°). The Acatita pole falls within a cluster of Late Triassic poles from Africa, South America, and North Americaas restored in North American coordinates. A major difficulty is distinguishing local, small-scale rotations, such as a gentle tilt ofthe pluton after magnetization, from regional events involving large-scale displacements. Rotations such as observed at Acatitaare suggested by synfolding magnetizations (Eocene in age) in the transverse sector of the Sierra Madre Oriental and by primarymagnetizations in Eocene volcanic rocks near Chihuahua. Therefore rotations of Coahuila Island may be a Cenozoic attributerelated to late Laramide deformation. Reconstructions of western equatorial Pangea should place the Coahuiltecano terrane at ornear its present position with respect to North America.